Rodzinne i społeczno-kulturowe uwarunkowania zaburzeń psychicznych. Analiza z perspektywy płci społeczno-kulturoioej - Frąckowiak-Sochańska, Monika (Wydawnictwo Naukowe UAM, 2010)
This article deals with social, cultural and family context of mental disorders. The author carries out her research from the perspective of gender studies, which is crucial regarding epidemiological statistical data and clinical observation. According to these two sources of information, there are several disorders "typical" for women (like: depression, anorexia, bulimia, anxiety disorders, histrionic personality disorder, dependent personality disorder and anxiety personality disorder) and for men (addictions to psychoactive substances, schizoid personality disorder, antisocial personality disorder). Symptoms of these mental diseases fit to stereotypes of men and women. That's why the symptoms can be interpreted in categories of "side effects" of socialization to nonflexible gender roles, which narrows opportunities of one's development.
Family and sociocultural factors in mental disorders. An analysis from the point of view of the sociocultural gender